Evaluasi formulasi dan pembuatan complete feed bahan pakan lokal daun kopi di peternak sapi potong Pasuruan Jawa Timur - Yudi Rustandi; Ismuladi Ismuladi; Mirna Silfiani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
This study aims to evaluate the preparation of feed formulations and the manufacture of complete feed fermentation based on local ingredients of coffee leaves. This research has three stages: preparation of complete feed formulations using trial and error methods using Microsoft Excel, trials of making complete feeds, and evaluating complete feed products. Evaluation is carried out on four aspects, namely; The nutritional composition of the complete feed has been fulfilled compared to the SNI for Beef Cattle Feed, which analyzed through a bar chart, the complete feed characteristic organoleptic test for texture, color, aroma, and presence of mushrooms through 24 respondents, palatability test carried out on six beef cattle belonging to farmer group members, and the economic aspect of the manufacturing cost component. The evaluation results show; the formulation and manufacture of complete feeds are by the SNI for Beef Cattle Feed. The characteristics of the compiled complete feeds are solid texture, not thick, not slimy and brittle, yellowish-green with sour aroma, and no fungus found are the characteristics of successful fermentation, preference test that all cows like complete feeds, and the results of the economic evaluation that each kilogram of complete feed costs Rp. 1,629.34, which is lower than the price of rice straw per kilogram.